2016
DOI: 10.1542/peds.2016-1533
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Video Assessment of Infant Sleep Environments

Abstract: BACKGROUND AND OBJECTIVE: Reports describing factors associated with sleep-related infant death rely on caregiver report or postmortem findings. We sought to determine the frequency of environmental risk factors by using nocturnal sleep videos of infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 27 publications
3
17
1
Order By: Relevance
“…This finding supports a prior study’s conclusion that parental motivation to bed-share trumped known risks of unsafe sleep [ 30 ]. The discovery of mothers who are practicing unsafe and ever-changing infant sleep practices is also consistent with studies demonstrating parental practice of unsafe sleep [ 5 , 6 , 31 , 32 ] and the changing of infant sleep environments throughout the night [ 33 ]. In this Facebook group, some mothers endorsed safe sleep and recommended following the AAP guidelines; however, other mothers believed they were following the recommendations and were actually creating dangerous infant sleep environments.…”
Section: Discussionsupporting
confidence: 58%
“…This finding supports a prior study’s conclusion that parental motivation to bed-share trumped known risks of unsafe sleep [ 30 ]. The discovery of mothers who are practicing unsafe and ever-changing infant sleep practices is also consistent with studies demonstrating parental practice of unsafe sleep [ 5 , 6 , 31 , 32 ] and the changing of infant sleep environments throughout the night [ 33 ]. In this Facebook group, some mothers endorsed safe sleep and recommended following the AAP guidelines; however, other mothers believed they were following the recommendations and were actually creating dangerous infant sleep environments.…”
Section: Discussionsupporting
confidence: 58%
“…This finding is consistent with those from another recently described cohort. 43 There are limitations to our analyses. The data come from a randomized controlled trial with 2 interventions.…”
Section: Discussionmentioning
confidence: 97%
“…22 -30 For example, studies assessing at-home compliance should probably use methodologies other than selfreport, as demonstrated by a recent study incorporating nocturnal video assessment. 23 Fourth, adherence to safe sleep guidelines requires resources (eg, access to cribs that meet safety standards and secure home environments in which to use them). Consistent with past research, 31 we found that mothers of SUID cases were less educated, younger, more likely to be unmarried, and more likely to be non-Hispanic African American than those of surviving infants.…”
Section: Discussionmentioning
confidence: 99%